2020
DOI: 10.1177/0825859720907419
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in End-of-Life Care in Older Mexican American Adults

Abstract: Mexican Americans (MAs), 1 of 10 subgroups of Latinos, are the largest and fastest growing Latino subgroup in the United States; yet, their access to end-of-life (EOL) care using hospice services is low. An investigation was needed into extant research-based knowledge about factors influencing EOL care decisions among MAs to guide health-care professionals in assisting MAs to make timely, acceptable, and satisfactory EOL care decisions. To determine whether gender was an influence on EOL decision-making among … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…Previous studies on older adults have shown that sex affects their perceptions of EOL care. 3,[21][22][23][24][25] One study indicated that women were more likely to refuse special life-sustaining treatment, such as CPR and ventilator, than men. 24 Another study in Switzerland showed that women had higher AD awareness and completion levels than men.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies on older adults have shown that sex affects their perceptions of EOL care. 3,[21][22][23][24][25] One study indicated that women were more likely to refuse special life-sustaining treatment, such as CPR and ventilator, than men. 24 Another study in Switzerland showed that women had higher AD awareness and completion levels than men.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with men, women had low overall LSPQ scores and tended to avoid antibiotics, CPR, surgery, and nasogastric tube feeding. Previous studies on older adults have shown that sex affects their perceptions of EOL care 3,21-25 . One study indicated that women were more likely to refuse special life-sustaining treatment, such as CPR and ventilator, than men 24 .…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, this can impede the use of palliative care services due to the difficulty families may have in transferring care responsibilities to health professionals (Ko et al, 2017). In addition, gender differences were noted among Latinos regarding EOL decision making (Crist et al, 2019; Ortiz-Dowling et al, 2020). Mexican American men more often refrained from expressing EOL desires, whereas women were more likely to delineate their EOL plans.…”
mentioning
confidence: 99%
“…Mexican American men more often refrained from expressing EOL desires, whereas women were more likely to delineate their EOL plans. Still, Latino family members maintain a crucial role in a peaceful death (Ortiz-Dowling et al, 2020).…”
mentioning
confidence: 99%